BAHAYA PENGGUNAAN FORMALIN SEBAGAI PENGAWET BAHAN MAKANAN - Hasnidar, Hasnidar; Tamsil, Andi; Akram, Andi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Fishery products are one of the products that have very limited durability and perishable so that the community, especially fishermen, preserve the product so that its freshness can last longer. One of the preservatives used is formalin, although it is very dangerous to human health. Some food products that contain formalin include: fresh fish, salted fish, tofu, wet noodles. Counseling on food safety needs to be continued widely to the public in various forms. This activity aims to educate and train partner groups on: 1) the dangers of formaldehyde on health; 2) characteristics of formalin food ingredients; 3) how to detect formalin foods; 4) eliminate / reduce formaldehyde levels in food products; 5) safe preservatives. The activities was carried out on February 7, 2019, in Desa Untia, Kecamatan Biringkanaya, Kota Makassar. The target group is fishermen and fisheries processors, as many as 23 people. The method used in service is counseling and training methods through lectures, discussions, and practice/training. The extension activity was attended by Untia village chiefs, local fisheries instructors, administrators of the All-Indonesian Fishermen Association (HNSI) and the target group. The activities went on smoothly and the target group enthusiastically attended counseling and training, because the knowledge/skills were needed to protect their families from the dangers of disease that could be caused by inappropriate use of formalin.